1996
DOI: 10.1136/ard.55.12.870
|View full text |Cite
|
Sign up to set email alerts
|

Relation between insulin-like growth factor-I concentrations, osteoarthritis, bone density, and fractures in the general population: the Chingford study.

Abstract: Objective-To assess the association between serum insulin-like growth factor-I (IGF-1) concentrations and osteoarthritis, and bone mineral density, and fractures in a large group of middle aged women from the general population. Methods-761 women aged 44-64 years from the Chingford study had serum IGF-I concentrations measured; hand, hip, spine, and anteroposterior weight bearing knee radiographs taken; and dual energy x ray absorptiometry (DEXA) scans of the hip and spine. X rays were scored using the Kellgre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 18 publications
3
41
1
Order By: Relevance
“…The risk profile for OA may vary depending on which joint or joint groups are involved. For instance, several well-established risk factors for knee OA, such as obesity and high bone mineral density, have not been shown consistently to increase the risk of hand OA (21)(22)(23)(24). In addition, the impact of risk factors may be different even among hand joints (25).…”
Section: Discussionmentioning
confidence: 99%
“…The risk profile for OA may vary depending on which joint or joint groups are involved. For instance, several well-established risk factors for knee OA, such as obesity and high bone mineral density, have not been shown consistently to increase the risk of hand OA (21)(22)(23)(24). In addition, the impact of risk factors may be different even among hand joints (25).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Trojan et al did not observe any associations between IGF-I levels and QOL measurements among 112 patients with post -polio syndrome (19). The mechanism of the potential influence of the IGF proteins on QOL is unclear, although the IGF/growth hormone axis has been correlated with improved organ functions, such as those of the brain (20) and heart (21,22) as well as bone density (23), which may lead to enhanced physical and psychological wellbeing. To our knowledge, no such studies have examined the relationship between this important family of proteins and QOL in cancer patients.…”
Section: Introductionmentioning
confidence: 92%
“…IGF-I can also be synthesized by chondrocytes. 27 This peptide is vital for childhood growth, but continues to have anabolic affects in adults. IGF-I is stimulated by growth hormones and helps cartilage maintain structural and functional integrity by inhibiting interleukin-1's ability to stimulate proteoglycan degredation.…”
Section: Insulin Growth Factor-imentioning
confidence: 99%
“…IGF-I is stimulated by growth hormones and helps cartilage maintain structural and functional integrity by inhibiting interleukin-1's ability to stimulate proteoglycan degredation. 27 However, under malnutrition conditions, hormone and receptor insensitivity, and failure to downstream signaling, can affect growth and stimulate damage to cartilage health. Past studies have shown that IGF-I can be important to the development of osteoarthritis and osteoporosis due to IGF-I being abundant in the cartilage and bone; therefore, it is suggested that it can prevent cartilage damage and the progression of osteoarthritis.…”
Section: Insulin Growth Factor-imentioning
confidence: 99%